Standard screening high-definition colonoscopy without any optimization device is no longer relevant: Time to move to optimized screening colonoscopy - Karsenti, David (Endoscopy International Open, 2024)
Optimizing the adenoma detection rate (ADR) is a major goal in colorectal cancer (CCR) screening, as it has long been established that ADR is inversely proportional to the risk of post-colonoscopy CRC occurrence. To achieve this goal, many optimization devices have been developed, and numerous randomized controlled trials have been conducted to evaluate the benefits of these devices compared with a "standard arm," which corresponds to date to high-definition white light (HD-WLI) colonoscopy. Numerous studies have confirmed the positive impact of various optimization devices, such as caps, computer-aided detection, and contrast-enhanced technologies. Moreover, the different ways in which the devices can impact ADR make them complementary. However, despite substantial and consistent data, practices remain unchanged, and HD-WLI colonoscopy, considered the "standard," is still routinely performed without any optimization devices. The objective of this viewpoint is to understand the barriers to change and to show why standard screening colonoscopy without the use of any optimization devices should no longer be considered relevant in 2024.
Keywords: Polyps / adenomas / ...; CRC screening; Endoscopy Lower GI Tract; Diagnosis and imaging (inc chromoendoscopy, NBI, iSCAN, FICE, CLE...); Quality and logistical aspects; Quality management